2011
DOI: 10.1016/j.oraloncology.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus types 16 and 18 in epithelial dysplasia of oral cavity and oropharynx: A meta-analysis, 1985–2010

Abstract: SUMMARY Human papillomavirus (HPV) types 16 and 18 are causally related to a sub-set of oral cavity and oropharyngeal squamous cell cancers. However, a clear estimate of the prevalence of HPV-16/18 in oral cavity and oropharyngeal dysplasia (OOPD) is not available. This literature review and meta-analysis was conducted to provide a prevalence estimate for HPV-16/18 in OOPD. Twenty-two studies that reported prevalence of HPV-16 and/or 18 in 458 OOPD lesions were analyzed. Meta-analysis was used to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
2
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 81 publications
6
77
2
11
Order By: Relevance
“…HPV detection rates were reported as 0% 17 and 80% 18 in studies on oral epithelial dysplasia, squamous cell carcinoma, and keratotic lesions performed in the 1990s using in situ hybridization and PCR, respectively; a more recent meta-analysis found a prevalence of 25% for HPV-16 and/or -18 by in situ hybridization and PCR. 12 Ha et al 10 detected the presence of HPV 16 DNA using real-time quantitative PCR in only 1 of 102 (1%) cases of oral premalignant lesions. Using PCR, D'Costa et al 19 detected HPV-16 in 34% of potentially malignant lesions and 31% of normal mucosa while Bouda et al 20 demonstrated high-risk HPV in oral epithelial dysplasia in all the five cases studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV detection rates were reported as 0% 17 and 80% 18 in studies on oral epithelial dysplasia, squamous cell carcinoma, and keratotic lesions performed in the 1990s using in situ hybridization and PCR, respectively; a more recent meta-analysis found a prevalence of 25% for HPV-16 and/or -18 by in situ hybridization and PCR. 12 Ha et al 10 detected the presence of HPV 16 DNA using real-time quantitative PCR in only 1 of 102 (1%) cases of oral premalignant lesions. Using PCR, D'Costa et al 19 detected HPV-16 in 34% of potentially malignant lesions and 31% of normal mucosa while Bouda et al 20 demonstrated high-risk HPV in oral epithelial dysplasia in all the five cases studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent meta-analysis calculated the prevalence of HPV-16 and/or HPV-18 in oral epithelial dysplasias to be 25%, these studies only identified the presence of HPV without investigating the expression of p16. 12 The purpose of this study is to evaluate a subset of oral epithelial dysplasias for the presence of transcriptionally active high-risk HPV subtypes and to further characterize the histological criteria for this condition. …”
mentioning
confidence: 99%
“…15,21 HPV, particularly high-risk types 16 and 18, is the major infectious cause of oropharyngeal cancer, especially of tonsil and tongue base primaries. 22,23 The proportion of HPV-associated oropharyngeal cancers is currently growing in the Western world, with prevalence estimates in the United States approaching 80%. 6 As a result, the ratio of oropharyngeal cancer to other HN cancers is around 30% in Western practice, which is substantially different from Asian population (12%) and Thailand (< 10%).…”
Section: Oropharyngeal Cancermentioning
confidence: 99%
“…For these reasons, some consider all HPV-related neoplasia of the tonsillar crypts as potentially malignant regardless of whether or not there is clear-cut histologic evidence of stromal invasion [17]. Numerous studies have also evaluated squamous dysplasia/carcinoma in situ of the surface mucosa of the upper aerodigestive tract (mainly oral cavity but also larynx) for the presence of HPV [18][19][20][21][22][23][24][25]. However, the rates of HPV detection are widely variable between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis including 15 studies of oral cavity dysplastic lesions found an HPV prevalence of 25.3 % [18]. Several studies evaluated premalignant squamous lesions by HPV DNA ISH but very few studies used HPV DNA ISH combined with p16 immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%